CRIMINAL SANCTIONS AGAINST CRIMINAL ACTORS WITH INTENTIONAL VIOLENCE FORCES A CHILD TO CONTINUOUSLY PERFORMS SEXUAL INTERCOURSE CASE STUDY DECISION NUMBER 5/PID.SUS/2018/PN SPG AT SAMPANG STATE COURT - Mohammad Mohammad; Insana Meliya Dwi Cipta Aprila Sari; Nizla Rohaya; Heriyono Tardjono (JHR (Jurnal Hukum Replik), 2022)
Every child is expected to be able to assume responsibility as the next generation of the nation, therefore children receive the widest opportunity to grow and develop optimally, both mentally, physically, and socially. The formulation of the problems in this research are: First, how are the Criminal Sanctions Against Criminal Actors in Decision Number 5/PidSus/2018/PN Spg? Second, how are the Judges' Consideration Factors in Imposing Sanctions for Criminal Acts in Decision Number 5/PidSus/2018/PN Spg? The theory used in this research is the theory of punishment. The research method used in this study is the empirical legal method. The conclusion of the study: first, the defendant Mohammad Hasbi Bin H. Usman was legally and convincingly proven to have committed a criminal act of violence or violence forcing a child to have sexual intercourse with him. Second, the defendant was provided a light sentence for he regretted his actions and the actor’s age remains young, therefore he is expected to have a future.